The Effect of E-Commerce, Sales Promotion, and Impulse Buying Behaviour of College Student in Indonesia - Ambo Paerah; Verawaty; Diah Ismayanti (Journal of Business and Behavioural Entrepreneurship, 2024)
The rapid development of information technology has significantly transformed various aspects of daily life, including shopping activities. E-commerce has become an integral part of everyday life, especially among the younger generation such as university students. In Indonesia, the usage of e-commerce platforms like Shopee, Tokopedia, and Lazada has dramatically increased, particularly during the Covid-19 pandemic. This study aims to analyze the impact of e-commerce and sales promotions on impulse buying behavior among Indonesian university students. Using a quantitative approach, we surveyed 400 students from various universities across Indonesia. Data were collected through online questionnaires and analyzed using SPSS for descriptive statistics and regression analysis. The findings reveal that website quality and sales promotions significantly influence impulse buying behavior. Higher website quality, characterized by easy navigation, attractive design, and secure transactions, enhances the likelihood of impulsive purchases. Moreover, sales promotions, including discounts, flash sales, and special offers, are found to be highly effective in triggering impulse buying. The combined effect of website quality and sales promotions further amplifies this behavior. These results suggest that e-commerce platforms targeting university students should optimize their website quality and employ attractive sales promotions to maximize the effectiveness of their marketing campaigns. Understanding these factors can provide valuable insights for e-commerce businesses to develop more effective and efficient marketing strategies tailored to the behavioral tendencies of young consumers.